2021
DOI: 10.1002/trc2.12189
|View full text |Cite
|
Sign up to set email alerts
|

Identifying relevant outcomes in the progression of Alzheimer's disease; what do patients and care partners want to know about prognosis?

Abstract: Background: Prognostic studies in the context of Alzheimer's disease (AD) mainly predicted time to dementia. However, it is questionable whether onset of dementia is the most relevant outcome along the AD disease trajectory from the perspective of patients and their care partners. Therefore, we aimed to identify the most relevant outcomes from the viewpoint of patients and care partners. Methods:We used a two-step, mixed-methods approach. As a first step we conducted four focus groups in the Netherlands to eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…In this study and others, 11,23,35 we found that patients want to know about their expected symptoms and progression rates. Furthermore, they indicated feeling left in ignorance after receiving the diagnosis 8 .…”
Section: Discussionsupporting
confidence: 52%
“…In this study and others, 11,23,35 we found that patients want to know about their expected symptoms and progression rates. Furthermore, they indicated feeling left in ignorance after receiving the diagnosis 8 .…”
Section: Discussionsupporting
confidence: 52%
“…In an earlier study, we showed that the trajectory of QoL of patients is an important outcome from the perspective of patients and their caregivers, in both dementia and pre-dementia stages [ 9 ]. A recent review of QoL in individuals with normal cognition, MCI, and AD dementia identified several gaps in literature [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main strength of this study is the prospective design with thorough and systematic annual clinical assessment. Secondly, this study estimated the trajectories not only in terms of cognitive decline but also incorporated QoL, IADL and caregiver burden over time, outcomes that patients and caregivers identified as relevant outcome measures 41 . Few limitations should be noted.…”
Section: Discussionmentioning
confidence: 99%